Acoustic Attenuation Performance Analysis and Optimisation of Expansion Chamber Coupled Micro-perforated Cylindrical Panel Using Response Surface Method - ALISAH, Mohamad Izudin; OOI, Lu-Ean; RIPIN, Zaidi Mohd; YAHAYA, Ahmad Fadzli; HO, Kelvin (Archives of Acoustics, 2021)
This paper describes boundary element method (BEM), experimental and optimization studies conducted to understand the potential of expansion tube coupled micro-perforated cylindrical panel (MPCP) to enhance the acoustic attenuation for in-duct noise control issues. Due to complex structure of the MPCP and for the correct prediction of acoustic attenuation, BEM is adopted on the basis of PLM Simcenter 3D software to compute the sound transmission loss (TL). As the MPCP is cylindrical in-shape with numbers of sub-milimeter holes, additive manufacturing based 3D printing was utilized for the model prototyping to reduce current design limitation and enabled fast fabrication. The TL measurement based two-load method is adopted for modal validation. Subsequently, a parametric studies of the MPCP concerning the perforation hole diameter, perforation ratio and depth of air space are carried out to investigate the acoustical performance. Optimization via response surface method (RSM) is used as it allows evaluating the effects of multiple parameters as required in this study. The model validation result shows that the error between the BEM and and measured values is relatively small and show a good agreement. The R-square value is 0.89. The finding from parametric study shows that a widen peak attenuation can be achieve by reducing the perforation hole diameter and one way to increase the transmission loss amplitude is by increasing the air cavity depth. Finally, the optimized MPCP model was adopted to the commercial vacuum cleaner for the verification. The sound pressure level (SPL) of the vacuum cleaner is significantly attenuated within the objective frequency of 1.7 kHz and its A-weighted SPL is reduced by 1.8 dB.